PELATIHAN ONLINE KARYAWAN INDUSTRI OTOMOTIF: KESIAPAN DIRI BERDASARKAN PERSPEKTIF CALON PESERTA - Tafakur, Tafakur; Dewi, Ayu Sandra; Solikin, Moch (Jurnal Pendidikan Vokasi Otomotif, 2023)
Currently, in response to rapid developments, many automotive industries are holding retraining for employees through online training. However, it is necessary to know the readiness of employees to participate. Therefore, this study aims to determine the profile of employee readiness to take part in online training in terms of various aspects. This research was conducted through a survey method. This data was obtained through online questionnaire on 89 employees. Proof of the validity of the instrument is done through content and construct validity. Data analysis used descriptive statistics and comparative tests. The results show that: First, the readiness of employees can be seen from aspects of basic computer skills, self-management, self-control, and willingness to learn. Second, the average readiness of employees is in the "very high" category. The online training readiness of employees is not significantly different from variations of respondents, both in terms of gender, age, training experience, length of work, and position in the workplace. Thus, the employees are ready to take online training in terms of their independent learning abilities.